Characteristics of the horizontal electric field associated with nearby lightning return strokes. (February 2017) - Yu, J.L.; Fan, Y.D.; Wang, J.G.; Qi, R.H.; Zhou, M.; Cai, L.; Cui, M.J.; Yuan, Z.J.
Abstract: There exists inherent difficulty in measuring the horizontal electric field ( E r ) associated with lightning return strokes due to the overshadowing effect of the vertical electric field component, not much progress in E r measurements were observed until now. In order to study the characteristics of E r associated with nearby lightning return strokes, the modified transmission-line model with linear current decay with height (MTLL) return stroke model and Finite Difference Time Domain (FDTD) method were used to calculate E r for 12 observation points with different distances (20, 50 100, and 200 m) away from the lightning channel and different heights (0, 10, and 20 m) above ground. Four characteristic parameters, namely, the return-stroke speed ( v ), the total length of the return stroke channel ( H ), the ground relative permittivity ( ε ) and the ground conductivity ( σ ), were considered. Results show that the polarity of E r changes between the ground level and the space. The influence intensity rank of the four characteristic parameters on E r at ground level is: σ > v > ε > H . The influence of the characteristic parameters on E r are more important for v ≤0.6c, H ≤6000 m and σ ≤2.5×10 −3 S/m. Highlights: Change is taken place on the polarity of Er between the ground and the space. The influence intensity rank on Er at ground is: σ>v>ε>H. The Er at ground is more sensitive to v and σ. The Er at 10 m and 20 m heights is more sensitive to v, H and σ.